Experimental transmission of Trypanosoma cruzi through the genitalia of albino mice - Leidi Herrera; Servio Urdaneta-Morales (Memorias do Instituto Oswaldo Cruz, 2001)
Trypanosoma cruzi is usually transmitted by contact with the excreta of infected Triatominae; among non-vectorial infections, direct transmission through coitus has been proposed. We investigated this possibility by instilling, through the external meatus of the vagina and the penis of previously anesthetized NMRI albino mice, blood of mice infected with strains isolated from Didelphis marsupialis (opossum, strain CO57), Rattus rattus (rat, strain CO22) and human (strain EP). Some animals were allowed to copulate the same day of the instillation. In other experiments, the strains were inoculated in the scrotum. To determine the effect of immunosuppression, some mice were treated with cyclophosphamide 30 days post-instillation. Controls were instilled orally and ocularly. Vaginal instillation with strain CO22 produced systemic infection with tropism to the heart, skeletal muscle, skin, duodenum, pancreas, ovary and sternum. Scrotal inoculation with strain EP likewise invaded liver, spleen, lung, lymph nodes and urogenital organs; while strain CO57 invaded skeletal and cardiac muscle, pancreas, testis, and vas deferens. Penile infection with strain CO22 was detected by xenodiagnosis. Immunosuppression did not increase parasitemia of vaginally infected mice or controls. Mating did not produce infection. Our results show that contact of blood trypomastigotes of T. cruzi with genital mucosa can produce blood and tissue infections. These results are discussed in relation to reports of frequent experimental tropism of T. cruzi toward urogenital organs.